Otimização de anodos para célula a combustível de óxido sólido fabricados por colagem de fitas - Rubens Moreira de Almeida (2014)
Solid oxide fuel cells (SOFC) are devices that convert chemical energy directly into electrical energy. The cermet of NiO/YSZ is the most common material used as anode in SOFCs. Tape casting is the main technique for the production of porous anode-support; however, one of the barriers to the development of SOFC is in the manufacture of flat, large-area anode-supported unit cell with suitable microstructure. This study aimed to optimize the anode support of NiO/YSZ in order to obtain flat,large-are anode-supported unit cell without cracks and suitable microstructure. From the synthesized powders of NiO and YSZ, slurry anode were prepared, which had the addition of n-octanol and the number of deaeration investigated. The anodes obtained by tape casting were burn-out, sintered and characterized by SEM. Cells of20 to 80 mm in diameter composed of anode, cathode and electrolyte had their electrical properties compared with a commercial cell from HC stack by impedance spectroscopy and linear voltammetry. The addition of n-octanol to the suspension, followed by deaeration resulted in an anode tape free of cracks and pinholes. The sintering pressure of 345 Pa provides flat anodes with 85 mm diameter. The SEM images confirmed the presence of pores in the anode and showed good grainmorphology. The analysis of linear voltammetry and impedance spectroscopy at 800 °C to cells of 20 and 80 mm indicated a specific area resistance of 1.0 and 0.95 /cm2 and power density of 582 mW/cm2 and 200 mW/cm2, respectively. The specific area resistance of HC Stack cell was 0.3 /cm2 and power density of 500 mW/cm2. These results show that other parts of the cell must also be optimized; however, the method of producing wide area anode is efficient. Overall, these results can be considered excellent for initial studies on fuel cells of high power.